Abdul Karim Soroush's "al-Qabd wa al-Bast" Theory as a Basis for the Development of Islamic Epistemology - Sufratman; Kholid Karomi (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to examine the thoughts of Abdul Karim Soroush’s, especially in his theory of al-Qabd and al-Bast as an effort to reconstruction of islamic religious reason. Based on library research, namely reference sources come from books, jurnals, articels, and other reference thet are relevant to the topic of discussion, this research uses a descriptive method. The result of this research is that the Abdul Karim Soroush’s theory of al-Qabd and al-Bast has three principles, namely Coherence and Corespondence, Interpenetration, and Evolution. Based on this principles, Abdul Karim Soroush’s has confirm that the position between religion and understanding of religion are two distinct entities. The position of religion is absolute and unchanging. While the understanding of religion is relative and dynamic. Therefore, Abdul Karim Soroush’s thoughts on the theory of al-Qabd and al-Bast, have very important and strategic implications and consequences in developing of religious reasoning in the contemporary era with changes that continue to take place dynamically.